An Equilibrium Model with Applications for some of the South American countries: Array - Ioan, Cătălin Angelo; Ioan, Gina (Acta Universitatis Danubius. Œconomica, 2020)
The model presented in this article is an adaptation of the IS-LM model for an open economy in which we took into account the temporal variable to more accurately determine the equilibrium levels of the macroeconomic indicators. We analyzed the periods during which the values of the indicators exceeded the level of equilibrium and we identified the possible causes that led to these situations.